The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21203/rs.3.rs-412539/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Head-to-Head Comparison of [68Ga]Ga-FAPI-04 and [18F]-FDG PET/CT in Evaluating the Extent of Disease in Gastric Adenocarcinoma

Abstract: Background[18F]-Fluorodeoxyglucose (FDG) positron emission tomography-computed tomography (PET/CT) may sometimes be suboptimal for imaging gastric adenocarcinoma. The recently introduced [68Ga]Ga-FAPI-04 (FAPI) PET/CT targets tumor stroma and has shown considerable potential in evaluating the extent of disease in a variety of tumors.MethodsWe performed a head-to-head prospective comparison of FAPI and FDG PET/CT in the same group of 13 patients with gastric adenocarcinoma who presented for either initial stagi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 9 publications
2
39
0
1
Order By: Relevance
“…Generally, the 68 Ga-FAPI-04 distribution at anastomotic sites was positively correlated with ¹⁸F-FDG and exhibited better imaging contrast than ¹⁸F-FDG, which is consistent with a previous finding for the detection of primary gastric cancer [12,24]. It has been reported that ¹⁸F-FDG PET SUVmax at anastomotic sites did not decrease over time in postoperative gastric cancer patients [6], and a similar pattern was observed in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Generally, the 68 Ga-FAPI-04 distribution at anastomotic sites was positively correlated with ¹⁸F-FDG and exhibited better imaging contrast than ¹⁸F-FDG, which is consistent with a previous finding for the detection of primary gastric cancer [12,24]. It has been reported that ¹⁸F-FDG PET SUVmax at anastomotic sites did not decrease over time in postoperative gastric cancer patients [6], and a similar pattern was observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…In preoperative patients, 68 Ga-FAPI-04 PET/CT imaging has recently been reported to have excellent performance in the diagnosis of primary gastrointestinal cancer (100% [10/10], [14/14], [19/19], [38/38]) compared to ¹⁸F-FDG PET/CT imaging (50.0-82.0%) [9,11,12,24], and also in detecting peritoneal carcinomatosis (100.0-97.7% vs. 0.0-72.1%) [10,24]. In this postoperative surveillance study, we discovered that the overall diagnostic performance of 68 Ga-FAPI-04 PET was better than ¹⁸F-FDG PET.…”
Section: Discussionmentioning
confidence: 99%
“…In the resectate from patient B, only signs of fibrosis and inflammation were found (ypT0N0). As a radiotracer, the FAPI has shown promising results for the detection and staging of various kinds of cancers, especially in those less suitable for evaluation with 18 F-FDG PET/CT such as gastrointestinal malignancies 1–5 . Because of elevated FAPI uptake in tissues affected by inflammatory processes including fibrotic remodeling, 6 FAPI PET/CT may also be an asset in the evaluation of nononcological conditions such as cardiac ischemic injury 7,8 and IgG4-related disease 9 .…”
mentioning
confidence: 99%
“…As a radiotracer, the FAPI has shown promising results for the detection and staging of various kinds of cancers, especially in those less suitable for evaluation with 18 F-FDG PET/CT such as gastrointestinal malignancies. [1][2][3][4][5] Because of elevated FAPI uptake in tissues affected by inflammatory processes including fibrotic remodeling, 6 FAPI PET/CT may also be an asset in the evaluation of nononcological conditions such as cardiac ischemic injury 7,8 and IgG4-related disease. 9 Concurrently, the non-malignancy-related FAPI uptake in degenerative processes, inflammation and in wound healing, 10 may cause difficulties when interpreting FAPI PET/CT in cancer patients.…”
mentioning
confidence: 99%
“…PET/CT imaging has been performed in various malignancy using FAP inhibitors (FAPIs) 2,3 . Recent studies have demonstrated that 68 Ga-FAPI-04 PET/CT has a superior detection rate than 18 F-FDG PET/CT for gastric cancer 4,5 . Also, FAPI uptake has been reported in nonmalignant diseases because of the chronic inflammation-induced transformation of fibroblasts to CAFs 6–9 .…”
mentioning
confidence: 99%